Leptin Promoted IL-17 Production from ILC2s in Allergic Rhinitis - Yanhui Wen; Qingxiang Zeng; Xi Luo; Renqiang Ma; Yiquan Tang; Wenlong Liu (Mediators of Inflammation)
Background. Interleukin-17 plays important roles in allergic diseases. Several studies proved that leptin promoted Th17 immune responses by inducing RORγt transcription. ILC2 is an important member of the early stage of immune response. Therefore, we aimed to explore the effect of leptin on the IL-17 production by ILC2 in AR in this study. Methods. Fifteen AR patients and fifteen healthy controls were enrolled. Serum leptin levels were measured, and their correlation with the frequency of IL-17+ ILC2 cells was analyzed using enzyme-linked immunosorbent assay (ELISA) and flow cytometry. ILC2 was stimulated by leptin, and the expression of IL-17, IL-5, and IL-13 was detected by ELISA. The correlated pathways were confirmed by real-time PCR. Results. We found that serum leptin and the frequency of IL-17-producing ILC2s in AR were significantly higher compared with those in controls. After being incubated with leptin, the frequency of IL-17+ ILC2 cells and IL-17 production from ILC2 was upregulated compared with that in controls. We also found that leptin induced RORγt and Ahr expression by ILC2. Moreover, leptin-induced IL-17-producing ILC2 concomitantly expressed IL-5 and IL-13. Conclusions. Our data provide preliminary evidence that leptin-induced IL-17 production from ILC2 cells is dependent on RORγt and Ahr expression and the blockade of leptin may be a promising target for the treatment of AR.